New Perspective of Calcium Oxide Nanoparticles in Forensic Science: Dr. Syeda Mona Hassan, Dr. Aftab Ahmad Malik, Hafiza Hadia Shehzad - DR Syeda Mona Hassan; Dr. Aftab Ahmad Malik; Hafiza Hadia Shehzad (International Journal for Electronic Crime Investigation, 2022)
Nano-technologies have wide applications in the field of forensic science. Nanotechnology is an important and powerful tool in most the areas including medicine, imaging, and forensic sciences. It has potential to make significant positive contribution in forensic science in crime detection. The present article focuses on the applications of CaO nanoparticles in developing and detecting the latent fingerprints. Fingerprint is considered noteworthy evidence in any crime scene, and nano-based techniques. An attempt was made to elucidate how nanotechnologies could be crucial in addressing current forensic investigation issues such as explosive detection, toxicological analysis, finger print analysis, forensic DNA analysis, detection of explosive residue, forensic nano trackers and drug facilitated crime.